Methods for Collecting Data Based Upon an Eastern Paradigm of Evaluation - Craig Russon (Journal of MultiDisciplinary Evaluation)
Background: This is one in a series of articles in which the authors attempt to relate Eastern philosophy to contemporary program planning and evaluation.